EFEKTIVITAS KEBIJAKAN ALOKASI DANA DESA UNTUK PENURUNAN STUNTING DI DESA LUBUK SANAI KECAMATAN XIV KOTO KABUPATEN MUKO-MUKO PROVINSI BENGKULU - Rahmadani Yusran; Rafiq Kurniawan (LPPM Universitas Abdurrab, 2024)
Government policies regarding the legal basis for reducing stunting have been planned for a long time and have been implemented. However, in its implementation, a number of more serious improvements are needed to achieve real realization. The problem of allocating funds for stunting prevention is in the spotlight in several regions in Indonesia. Seeing how important it is to allocate funds for reducing stunting in an area, such as the current research theme in a village, namely Lubuk Sanai Village, XIV Koto District, Mukomuko Regency. This village shows a serious commitment to tackling stunting by allocating 8% of village funds in 2022 to carry out special interventions in this area. This research aims to analyze the implementation of village fund allocation policies to reduce stunting in Lubuk Sanai village. In this research, the author uses a qualitative approach using a descriptive method that describes the background of observations, actions, people and conversations obtained in the field regarding the effectiveness of Lubuk Sanai village fund allocation for efforts to reduce stunting. The research results show that although this program has had a positive impact on efforts to reduce stunting rates, there are a number of challenges that must be faced. The cash assistance and healthy food supplies provided have helped meet the nutritional needs of pregnant, breastfeeding mothers and stunted children, however the amount of assistance fluctuates due to other development priorities affecting the effectiveness of this program. In addition, the implementation of the village fund allocation policy to reduce stunting in Lubuk Sanai Village has gone through various evaluation stages, starting from initial design with Rembuk Stunting activities to ongoing monitoring and evaluation. The Stunting Consultation involves various stakeholders to ensure policies are data-based and meet field needs.